Pengaruh Literasi Keuangan, Parental Income, Locus Of Control, Dan Lingkungan Sosial Terhadap Perilaku Keuangan Pada PAC IPNU IPPNU Wringinanom, Kabupaten Gresik - Sa’diyah, Shofiatus; Trihastuti, Rr. Adiati (Cattleya Darmaya Fortuna, 2025)
This study aims to evaluate the influence of financial literacy, parental income, locus of control, and social environment on the financial behavior of PAC IPNU IPPNU members in Wringinanom District, Gresik Regency. Distributing questionnaires to collect data from organization members and analyzing it via multiple linear regression with SPSS 26.The findings reveal that financial literacy has a significant effect on financial behavior. Parental income also significantly influences financial behavior, as does the locus of control, which has a notable impact on financial behavior. Additionally, the social environment is proven to reveal a significant effect on financial behavior. Collectively, financial literacy, parental income, locus of control, and social environment jointly influence financial behavior.